Domestic preparation and orgatization towards the negotiations of the Peru-USA Free Trade Agreement - Chan Sánchez, Julio (2018)
This article deals with the preparation process for the negotiations of the Free Trade Agreement between Peru and the United States. It also deals with the internal coordination process developed in order to successfully negotiate with the United States, as well as to obtain support of the relevant domestic actors.It is argued that the activities related to preparation, organization, coordination and information were a fundamental element for the success of these negotiations with our most important trade partner of the time, being also the first free trade agreement negotiated outside Latin America.